The Inter-Trimester Variation and Prognostic Value of Creatinine, Cystatin C and Uric Acid in Preeclamptic Patients: A Retrospective Study - Junpeng Jing; Junlong Wang; Gaifeng Hu; Xiaofen Wei; Jin Li; Wanyuan Qin (Clinical and Experimental Obstetrics & Gynecology)
Background: This study aimed to evaluate the clinical significance of maternal serum creatinine, cystatin C, and uric acid levels in relation to fetal death in pregnant women with preeclampsia. Methods: This retrospective study evaluated 708 women with preeclampsia, and 738 healthy pregnant women were selected as control. Medical records were reviewed to collect obstetric, neonatal, and biochemical data, including creatinine, cystatin C, and uric acid concentrations. Results: Maternal serum creatinine, cystatin C, and uric acid concentrations were significantly higher in the preeclamptic group than in the control (p < 0.05). Preeclamptic women in the fetal death group had significantly higher creatinine levels during their second and third trimesters, and higher uric acid concentrations throughout the pregnancy compared to the fetal survival group. Preeclamptic patients were divided into four groups based on quartiles of uric acid levels. The overall fetal survival rate in patients with upper-quartile uric acid concentrations was significantly lower than those with low uric acid levels during pregnancy. Multivariate logistic regression analysis revealed that uric acid concentration was a significant risk factor for fetal death in the first and second trimesters in the preeclamptic group (p < 0.05). Conclusions: In pregnant women with preeclampsia, fetal death was associated with upper-quartile uric acid concentrations in the first and second trimesters. Uric acid levels can be an indicator of fetal death in the early and middle stage of pregnancy.